The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.1007/s12264-013-1442-8
|View full text |Cite
|
Sign up to set email alerts
|

Orexin A attenuates the sleep-promoting effect of adenosine in the lateral hypothalamus of rats

Abstract: Orexin neurons within the lateral hypothalamus play a crucial role in the promotion and maintenance of arousal. Studies have strongly suggested that orexin neurons are an important target in endogenous adenosine-regulated sleep homeostasis. Orexin A induces a robust increase in the firing activity of orexin neurons, while adenosine has an inhibitory effect. Whether the excitatory action of orexins in the lateral hypothalamus actually promotes wakefulness and reverses the sleep-producing effect of adenosine in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 36 publications
(46 reference statements)
0
16
1
1
Order By: Relevance
“…We showed that slow continuous infusion of orexin-A via intrathecal route did not appreciably alter the sleep/wake profile of animals. These observations are in contrast with previous reports where a robust increase in arousal was observed in mice (17,34) and rats (35) upon ICV administration of orexin. These latter studies used bolus injections, thus rapidly and transiently increased the concentration of peptide at the vicinity of orexin receptors, resulting in an acute increase in wakefulness.…”
Section: Discussioncontrasting
confidence: 99%
“…We showed that slow continuous infusion of orexin-A via intrathecal route did not appreciably alter the sleep/wake profile of animals. These observations are in contrast with previous reports where a robust increase in arousal was observed in mice (17,34) and rats (35) upon ICV administration of orexin. These latter studies used bolus injections, thus rapidly and transiently increased the concentration of peptide at the vicinity of orexin receptors, resulting in an acute increase in wakefulness.…”
Section: Discussioncontrasting
confidence: 99%
“…As Orx has been reported to stimulate the glutamatergic neurons in the PH, a synergistic interaction between Orx-ergic glutamatergic neurons has been proposed to maintain arousal [32]. Also, Orx activated glutamate from the subcortical areas may contribute to maintain wakefulness [33]. Further, as the PH is known to be responsible for maintenance of homeostasis [13], we propose that normally the Orx-A may participate in maintaining sleep-waking homeostasis, which is disturbed upon REMSD resulting in elevated level of Orx-A or vice versa.…”
Section: Discussionmentioning
confidence: 99%
“…Local injection of the selective A 1 receptor antagonist 1,3-diethyl-8-phenylxanthine (DPX) enhances activity in hypocretinergic neurons and promotes waking [112]. By contrast, activation of A 1 receptors in the LHA by adenosine promotes sleep [113,114]. These findings illustrate that adenosine may contribute to sleep-wake regulation, as well as metabolism and feeding by modulating the activity of hypocretin neurons in vivo.…”
Section: Metabolism and Adenosinementioning
confidence: 98%